The Importance of Good Constitution for Resulting Good Governance and Clean Goverment - Yoyon Mulyana Darusman; Bambang Wiyono; Guntarto Widodo (Jurnal Dinamika Hukum, 2019)
The existence of the Constitution in the State as the Social Contract to born of the State, this statement base onSocrates (Era the 3 rd before Messiah) as one of the other philosophy of Greek, so that in the practicing of born orestablish of the States in the world, beginning by compromise of the Constitution of the State.